1994
DOI: 10.1128/iai.62.2.639-643.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tracheal cytotoxin from Bordetella pertussis on human neutrophil function in vitro

Abstract: The infiltration of neutrophils which phagocytose and kill microorganisms is an important defense mechanism against infections of the airways. Bordetella pertussis is a human respiratory pathogen which colonizes ciliated epithelium, causing whooping cough. We have investigated the effects of the peptidoglycan fragment tracheal cytotoxin (TCT) of B. pertussis on human neutrophil function in vitro. TCT (10-6 to 10-8 M) was toxic for human neutrophils, as measured by lactate dehydrogenase release and levels of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…It is likely that the Ptx-mediated decrease in chemokine release also contributed to the reduced early infiltration of leukocytes observed in earlier studies (Meade et al, 1985;Spangrude et al, 1985). In addition to Ptx, TCT has also been shown to inhibit neutrophil chemotaxis, at least in vitro (Cundell et al, 1994), which may also partially contribute to this effect.…”
Section: Recruitment Of Immune Cellsmentioning
confidence: 99%
“…It is likely that the Ptx-mediated decrease in chemokine release also contributed to the reduced early infiltration of leukocytes observed in earlier studies (Meade et al, 1985;Spangrude et al, 1985). In addition to Ptx, TCT has also been shown to inhibit neutrophil chemotaxis, at least in vitro (Cundell et al, 1994), which may also partially contribute to this effect.…”
Section: Recruitment Of Immune Cellsmentioning
confidence: 99%
“…In addition, peptidoglycan from Gram‐positive bacteria induces meningeal inflammation in rabbits injected intracisternally 4. In cell culture models, early reports identified the immunomodulatory properties of peptidoglycan and/or subfragments of peptidoglycan towards monocytes, macrophages 5, 6, neutrophils 7 and respiratory epithelial cells 8. Pro‐inflammatory cytokines such as IL‐1, IL‐6 and TNF‐α are known to be released by macrophages following exposure to either Gram‐positive bacterial peptidoglycan or soluble muramyl peptides derived from polymeric peptidoglycan (for a review, see 9).…”
Section: Study Of the Role Of Peptidoglycan In Innate Immunity Durimentioning
confidence: 99%
“…82,83 This hypothesis was later confirmed in the pioneering studies of Rosenthal, Goldman and others, who demonstrated the toxic effects of these soluble peptidoglycan fragments on host cells. [84][85][86][87][88] The Gram-negative bacterial pathogens, Neisseria gonorrhoea and Bordetella pertussis, were subsequently shown to release tetra and tri forms of mDAP-containing fragments into the external milieu. 84,[86][87][88] We now know that these forms are specifically recognized by mouse and human forms of NOD1, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[84][85][86][87][88] The Gram-negative bacterial pathogens, Neisseria gonorrhoea and Bordetella pertussis, were subsequently shown to release tetra and tri forms of mDAP-containing fragments into the external milieu. 84,[86][87][88] We now know that these forms are specifically recognized by mouse and human forms of NOD1, respectively. 9 Interestingly, much later reports described the IL-8inducing activities of cell-free supernatants of the pathogens, Campylobacter jejuni 89 and Pseudomonas aeruginosa, 90 on non-phagocytic cells.…”
Section: Discussionmentioning
confidence: 99%